ECONOMIC VALUE ADDED (EVA) AS A FINANCIAL PERFORMANCE MEASUREMENT METHOD - Dwi Susanti, Rizki Aprilia; Hayuningtyas, Ruri Fitria; Astuti, Farida Kusuma (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
Purpose: This study aims to identify and analyze the financial performance of the cosmetics industry from 2018 to 2022 using the Economic Value Added (EVA) method. This method was chosen because it accurately reflects the actual profit achieved by a company, as it accounts for the cost of capital. Additionally, the EVA method is highly practical for application. The chosen research method is descriptive quantitative, with data analysis using the Economic Value Added (EVA) financial performance calculation method, which consists of five stages of analysis: (1) Net Operating Profit After Tax (NOPAT); (2) Invested Capital; (3) Weighted Average Cost Of Capital (WACC); (4) Capital Charges; and (5) Economic Value Added (EVA). Results: Only three companies demonstrated good performance, namely PT. Kino Indonesia Tbk, PT. Victoria Care Indonesia Tbk, and PT. Unilever Indonesia Tbk. During the period from 2018 to 2020, PT. Kino Indonesia Tbk, PT. Victoria Care Indonesia Tbk, and PT. Unilever Indonesia Tbk managed to achieve operating profits higher than tax expenses and operating profits exceeding capital costs, thus meeting the expected rate of return by investors.